Test of Some Varieties and Application Pesticides of Cloves Leaves to Eliminate Worm in Corn (Zea mays L). - Nasution , Erti Kumala Indah; Harahap, Samsinar; Bisri, Ahmad; Nasution, Koirul Fadli (Jurnal Online Pertanian Tropik, 2021)
The purpose of this research is to find out to determine the test of several varieties and the application of vegetable pesticides for clove leaves for Eradicating Leaf worms on Corn Plants (Zea mays L). From the results of statistical data analysis, the treatment of several varieties showed no significant effect on the parameters of plant height 3, 5, and 9 weeks after planting, Â diameter 3 and 5 weeks after planting, ear weight per sample, and ear weight per plot, but had no significant effect on the parameters. Plant height at 7 weeks after planting, stem dimensions 7 and 9 weeks after planting, and intensity of leaf caterpillar pests at 3, 5, 7, and 9 weeks after planting. From the results of statistical data analysis, clove leaf vegetable pesticide treatment showed a significant effect on the parameters of plant height at 5 weeks after planting, stem diameter 3, 5, 7, and 9 weeks after planting, but had no significant effect on plant height parameters aged 3, 7 and 9 weeks after planting, ear weight per sample, ear weight per plot and intensity of attack of leaf worm pests aged 3, 5, 7 and 9 weeks after planting. From the results of statistical data analysis, the interaction between the two treatments above shows an insignificant effect on all observed parameters.